Potential inhibitory effects of compounds ZK-PI-5 and ZK-PI-9 on trehalose and chitin metabolism in Spodoptera frugiperda (J. E. Smith) - Zhong, Fan; Yu, Liuhe; Jiang, Xinyi; Chen, Yan; Wang, Sitong; Chao, Lei; Jiang, Zhiyang; He, Biner; Xu, Caidi; Wang, Shigui; Tang, Bin; Duan, Hongxia; et al. (Frontiers in Physiology, 2023)
Spodoptera frugiperda is an omnivorous agricultural pest which is great dangerous for grain output. In order to investigate the effects of potential trehalase inhibitors, ZK-PI-5 and ZK-PI-9, on the growth and development of S. frugiperda, and to identify new avenues for S. frugiperda control, we measured the content of the trehalose, glucose, glycogen and chitin, enzyme activity, and gene expression levels in trehalose and chitin metabolism of S. frugiperda. Besides, their growth and development were also observed. The results showed that ZK-PI-9 significantly reduced trehalase activity and ZK-PI-5 significantly reduced membraned-bound trehalase activity. Moreover, ZK-PI-5 inhibited the expression of SfTRE2, SfCHS2, and SfCHT, thus affecting the chitin metabolism. In addition, the mortality of S. frugiperda in pupal stage and eclosion stage increased significantly after treatment with ZK-PI-5 and ZK-PI-9, which affected their development stage and caused death phenotype (abnormal pupation and difficulty in breaking pupa). These results have provided a theoretical basis for the application of trehalase inhibitors in the control of agricultural pests to promote future global grain yield.